Vibrations Diagnosis and Condition Monitoring of Centrifugal Pumps at Al-Brega Oil Company - Ezedine G. Allaboudi; Khaled M. Ahmida (African Journal of Advanced Pure and Applied Sciences, 2025)
This study focuses on diagnosing and analyzing faults in centrifugal pumps at Al-Brega Oil Company using vibration monitoring techniques. It primarily identifies common issues such as misalignment, imbalance, and bearing failures, which can cause significant operational inefficiencies and expensive repairs. The research methodology employs overall velocity, shock pulse, and spectrum analysis via the VIBXpert device, demonstrating effectiveness in early fault detection before problems escalate. Results are compared against ISO standards to evaluate the condition and performance of the pumps. The findings highlight the importance of routine monitoring to minimize downtime and maintenance costs by detecting faults early. Moreover, the study offers valuable insights into enhancing maintenance strategies for more reliable and efficient operation of industrial pumping systems.